2020
DOI: 10.3390/nano10122556
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal/Multifunctional Nanomaterials in (Bio)electrochemistry: Now and in the Coming Decade

Abstract: Multifunctional nanomaterials, defined as those able to achieve a combined effect or more than one function through their multiple functionalization or combination with other materials, are gaining increasing attention in the last years in many relevant fields, including cargo targeted delivery, tissue engineering, in vitro and/or in vivo diseases imaging and therapy, as well as in the development of electrochemical (bio)sensors and (bio)sensing strategies with improved performance. This review article aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 198 publications
0
5
0
Order By: Relevance
“…Nanoformulations can be helpful in bioimaging and diagnosis techniques, for example as contrast agents in magnetic resonance imaging (MRI) or positron emission tomography (PET) tracers [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The main advantage of nanomedicines lies in their multimodality [ 18 , 19 ]. Nanomaterials simultaneously provide targeted detection and therapeutic capabilities, giving rise to a theranostic approach [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoformulations can be helpful in bioimaging and diagnosis techniques, for example as contrast agents in magnetic resonance imaging (MRI) or positron emission tomography (PET) tracers [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The main advantage of nanomedicines lies in their multimodality [ 18 , 19 ]. Nanomaterials simultaneously provide targeted detection and therapeutic capabilities, giving rise to a theranostic approach [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research studies and reviews have reported that precious metal nanomaterials dispersed on numerous metal oxide supports as metal nanocomposites, which are catalytically more active for various electrochemical reactions [17,[19][20][21][22]. In some cases, metal oxide nanomaterials are used as support materials for embedding noble metallic nanoparticles, and in particular Au, Pt, and Ru nanoparticles, dispersed on an oxide support often showed much higher catalytic activity than the single-component nanoparticles [10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their unique properties that are different from traditional materials, nanomaterials are making a splash in sensor modifications and can improve the analytical performance of sensors [ 41 , 42 ]. Graphene, a new material consisting of carbon atoms tightly stacked into a monolayer two-dimensional honeycomb structure [ 43 ], has been attracting widespread attention since it was first stably prepared by micromechanical exfoliation in 2004 [ 44 ].…”
Section: Introductionmentioning
confidence: 99%